The Role of Creative Writing Education in Developing the Creative Economy: A Comparative Study of Vocational High Schools in Indonesia and Malaysia - Roni Sulistiyono; Pujiati Suyata; Desta Rizky Kusuma; Norjietta Julita Binti Taisin; Robe'ah Yusuf (Alinea: Jurnal Bahasa, Sastra dan Pengajaran, 2026)
The increasing demand for twenty-first-century competencies, including creativity, productivity, and entrepreneurial capacity, has prompted a reorientation of language education toward more adaptive and context-responsive pedagogies. Within this shift, creative writing is increasingly recognized as a strategic means of preparing students for the evolving demands of the contemporary workforce. However, empirical evidence linking creative writing instruction to career readiness in the creative economy remains limited, particularly in cross-national comparative contexts. This study investigates the contribution of creative writing instruction to students’ career readiness in the creative economy sectors of Indonesia and Malaysia. Employing a quantitative approach with an ex-post facto design, data were collected through a structured questionnaire measuring students’ perceptions of creative writing instruction, along with indicators of career readiness, including academic aspirations, resilience, and awareness of career opportunities. The data were analyzed using descriptive and comparative statistical techniques. The findings indicate that creative writing instruction is associated with the development of productive literacy, creativity, and entrepreneurial orientation. Comparative analysis further reveals that Malaysian students tend to demonstrate higher levels of academic aspiration and resilience, whereas Indonesian students exhibit stronger adaptive capacities in responding to contextual learning constraints. These findings suggest that creative writing instruction extends beyond linguistic development and plays a meaningful role in supporting students’ transition into the creative economy. The study provides empirical support for integrating creative literacy and entrepreneurship into vocational language curricula to enhance students’ career readiness.